M1 Macrophages Are Predominantly Recruited to the Major Pelvic Ganglion of the Rat Following Cavernous Nerve Injury - Matsui, Hotaka; Sopko, Nikolai A.; Hannan, Johanna L.; Reinhardt, Allison A.; Kates, Max; Yoshida, Takahiro; Liu, Xiaopu; Castiglione, Fabio; Hedlund, Petter; Weyne, Emmanuel; Albersen, Maarten; Bivalacqua, Trinity J. (Journal of Sexual Medicine, 2017)
Introduction Neurogenic erectile dysfunction is a common sequela of radical prostatectomy. The etiology involves injury to the autonomic cavernous nerves, which arise from the major pelvic ganglion (MPG), and subsequent neuroinflammation, which leads to recruitment of macrophages to the injury site. Currently, two macrophage phenotypes are known: neurotoxic M1 macrophages and neuroprotective M2 macrophages. Aim To examine whether bilateral cavernous nerve injury (BCNI) in a rat model of erectile dysfunction would increase recruitment of neurotoxic M1 macrophages to the MPG. Methods Male Sprague-Dawley rats underwent BCNI and the MPG was harvested at various time points after injury. The corpora cavernosa was used to evaluate tissue myographic responses to electrical field stimulation ex vivo. Quantitative real-time polymerase chain reaction was used to examine the gene expression of global macrophage markers, M1 macrophage markers, M2 macrophage markers, and cytokines and chemokines in the MPG. Mathematical calculation of the M1/M2 index was used to quantify macrophage changes temporally. Western blot of MPG tissues was used to evaluate the protein amount of M1 and M2 macrophage markers quantitatively. Immunohistochemistry staining of MPGs for CD68, CD86, and CD206 was used to characterize M1 and M2 macrophage infiltration. Main Outcome Measures Corpora cavernosa responsiveness ex vivo; gene (quantitative real-time polymerase chain reaction) and protein (western blot) expressions of M1 and M2 markers, cytokines, and chemokines; and immunohistochemical localization of M1 and M2 macrophages. Results BCNI impaired the corporal parasympathetic-mediated relaxation response to electrical field stimulation and enhanced the contraction response to electrical field stimulation. Gene expression of proinflammatory (Il1b, Il16, Tnfa, Tgfb, Ccl2, Ccr2) and anti-inflammatory (Il10) cytokines was upregulated in the MPG 48 hours after injury. M1 markers (CD86, inducible nitric oxide synthase, interleukin-1β) and M2 markers (CD206, arginase-1, interleukin-10) were increased after BCNI in the MPG, with the M1/M2 index above 1.0 indicating that more M1 than M2 macrophages were recruited to the MPG. Protein expression of the M1 macrophage marker (inducible nitric oxide synthase) was increased in MPGs after BCNI. However, the protein amount of M2 macrophage markers (arginase-1) remained unchanged. Immunohistochemical characterization demonstrated predominant increases in M1 (CD68+CD86+) macrophages in the MPG after BCNI. Conclusion These results suggest that an increase in M1 macrophage infiltration of the MPG after BCNI is associated with impaired neurogenically mediated erectile tissue physiology ex vivo and thus has significant implications for cavernous nerve axonal repair. Future studies are needed to demonstrate that inhibition of M1 macrophage recruitment prevents erectile dysfunction after CNI.
Keywords: Erectile Dysfunction; Macrophage Markers; Major Pelvic Ganglion; Neuroinflammation; Neuroprotective; Peripheral Nerve Injury